Self-Regulation Interventions for Enhancing Self-Care Outcomes in Patients with Coronary Heart Disease: A Systematic Review - Israh Israh; Tuti Herawati; Muhammad Adam (Universitas Ahmad Dahlan, 2026)
Background: Coronary Heart Disease (CHD) remains a major contributor to global morbidity and mortality, requiring long-term self-care management following hospital discharge. Self-regulation has emerged as an important cognitive-behavioral framework that strengthens patients’ autonomy, symptom monitoring, and adherence to health-related behaviors. Objective: This systematic review aimed to evaluate the effectiveness of self-regulation programs in improving self-care among post-discharge patients with CHD. Methods: A systematic review was conducted following the PRISMA guidelines. Literature searches were performed across five electronic databases, including PubMed, ClinicalKey Nursing, ScienceDirect, SAGE Journals, and ProQuest, covering publications from 2022 to 2025. Eligible studies were randomized controlled trials (RCTs) involving CHD patients receiving self-regulation-based interventions targeting self-care outcomes. Ten RCTs met the inclusion criteria, involving 668 participants in intervention groups and 665 participants in control groups. Results: The findings consistently demonstrated that self-regulation interventions, including digital and telehealth-based monitoring, cognitive behavioral therapy (CBT), goal-setting strategies, and family-supported approaches, significantly improved medication adherence, physical activity, symptom management, self-care behaviors, and quality of life. Technology-assisted interventions and family involvement showed particularly strong effects in promoting sustained self-management. Conclusion: Self-regulation programs are effective in enhancing self-care and health-related outcomes among patients with CHD after hospitalization. Integrating technology-based monitoring and family-centered support into cardiac rehabilitation programs may strengthen long-term disease management and reduce adverse clinical outcomes.